Analytical Study from Risale-i Nur by Imam Bediuzzaman Said Nursi on the formation of a peaceful mind - Fatah Yasin, Raudlotul Firdaus; Fatah Yasin, Muhammad Muthi’ul Haqq; Fatah Yasin, Mohamad Dhiya'ul Hafidh (International Scientific Research Association (ISCIRA), 2024)
Said Nursi was a figure who brought tides of reform in the era after the fall of Islamic Caliphate, until he was honored with the title of Bediuzzaman. In facing the assassination of Muslim identity by the secular Turkish, he became the center and torch for the Turkish Muslim community to find light. However, his prominence is not limited to Turkiye only, but is also a reference for the Muslim community all over the world, until today. The results of his works, especially the Epistles of Light, are very effective for those who are experiencing mental confusion, mental and emotional stress, to free themselves by ‘exiting the narrow world to the wide world and the hereafter'. This provides a solution that the concept of a peaceful and independent mind which is brought in the form of analogy and rational discussion is suitable to be applied in the context of mental health which is getting worse today. This study aims to analyze the concept of building a peaceful and independent mind from Bediuzzaman Said Nursi's Epistles of Light. This qualitative study uses inductive methods to identify the most important contents of the work, which are related to the process of building a peaceful mind. The study concluded that al-Nursi's concept of a peaceful and independent mind is a holistic point of view towards the text of the Qur'an and Sunnah, especially when he designed the formation starting from the realm of the spirit and the womb, and so on, and linked to the human science. The main impact of this study is the formation of a concept of a peaceful mind that is suitable to be applied in the context of the mental health crisis today.